Rapid Exhumation of Earth's Youngest Exposed Granites Driven by Subduction of an Oceanic Arc - Spencer, Christopher; Danišík, M.; Ito, H.; Hoiland, C.; Tapster, S.; Jeon, H.; McDonald, B.; Evans, Noreen (American Geophysical Union, 2019)
Exhumation of plutonic systems is driven by a range of mechanisms including isostatic, tectonic, and erosional processes. Variable rates of plutonic exhumation in active subduction systems may be driven by idiosyncrasies of regional geology or by first-order tectonic features. We report new age, isotope, and low-temperature thermochronology constraints of granitoids from the Hida Mountains of central Japan that constrain the highest rates and magnitude of plutonic rock exhumation within the Japan and one of the highest worldwide. This extreme exhumation is centered on the apex of a lithospheric scale anticlinorium associated with the subduction of the Izu-Bonin oceanic arc. The spatial and temporal relationship between the exhumation of these Pleistocene plutons and the subducting/accreting Izu-Bonin oceanic arc links the plate-scale geodynamics and regional exhumation patterns. Identifying thermochronological anomalies within magmatic arcs provides an opportunity to identify ancient asperities previously subducted and responsible for rapid exhumation rates within ancient subduction systems.